2006
DOI: 10.1088/1748-6041/1/4/010
|View full text |Cite
|
Sign up to set email alerts
|

Study on the preparation of collagen-modified silk fibroin films and their properties

Abstract: Blended films were prepared from a silk fibroin (SF) solution by adding a small amount of type I collagen (<5%). The mechanical properties of the wet films modified by collagen were improved obviously. The elongation at break reached 42%, and the smaller contact angles revealed that modified films had better hydrophilicity. 1% heparin was also added to modify the SF films to further improve the in vitro antithrombogenecity. The internal structure of the modified SF films was investigated with scanning electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 33 publications
2
13
0
1
Order By: Relevance
“…With the content of silk fibroin increase, the tensile stress, as well as the elastic modulus of the membranes decreased. However, the elongation at break of the membranes increased with the increase of the silk fibroin, which was consistent with the conclusion made by others . Specifically, the tensile strength of CS05 (1.14 ± 0.05 MPa) was nearly same to that of Col (1.11 ± 0.06 MPa), showing no significant difference ( p = 0.40).…”
Section: Resultssupporting
confidence: 91%
“…With the content of silk fibroin increase, the tensile stress, as well as the elastic modulus of the membranes decreased. However, the elongation at break of the membranes increased with the increase of the silk fibroin, which was consistent with the conclusion made by others . Specifically, the tensile strength of CS05 (1.14 ± 0.05 MPa) was nearly same to that of Col (1.11 ± 0.06 MPa), showing no significant difference ( p = 0.40).…”
Section: Resultssupporting
confidence: 91%
“…The molecular conformation of B. mori silk fibroin is characterized by β-sheet absorption peaks around 1630, 1530 and 1240 cm −1 , random coil conformation absorption peaks at 1650 or 1645, 1550 and 1230 cm −1 , and an α-helix absorption peak around 1655 cm −1 [15,22]. Tang and colleagues had previously reported that the intensity of peaks around 3300 cm -1 (data not shown here) fluctuate in response to hydrogen bonds [23]. …”
Section: Resultsmentioning
confidence: 79%
“…These disadvantages can be addressed by the use of low molecular weight heparins instead of unfractionated heparin [39, 41]. We used the low molecular weight heparin Tinzaparin to functionalize silk; no other previous study has used this fractionated heparin in combination with silk [22, 23, 25, 42]. …”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have applied various functional coagulation tests to analyse heparin modified silk films or fibers (e.g., [22, 23, 25, 42]). All these studies reported improvement of the clotting parameters but did not examine the inflammatory response towards silk and its potential effect on the anticoagulant state of endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation